Demand for Water Tourism by Rafting in the Upper Northeastern Region 1 of Thailand - WAIYAWET, Supreeya; NONTHAPOT, Sakkarin (Journal of Environmental Management and Tourism, 2023)
This research aimed to 1) study the components for the demand for water tourism by rafting among tourists in the New Normal, and 2) study the factors of water tourism by rafting among tourists in the New Normal in the Upper Northeastern Region 1, Thailand. The data was collected from 400 samples from five Northeastern provinces, i.e. , Udon Thani, Nong Khai, Loei, Nong Bua Lam Phu, and Bueng Kan; obtained by provincial quota sampling with 80 samples per province. Convenience sampling was also used. Exploration factor analysis (EFA) and confirmatory factor analysis (CFA) was conducted by using ADANCO ver.2.3 as per the objectives. It was found that 1) the components for the demand for water tourism by rafting could be categorized into one group with five factors, i.e. , rafting duration, previous rafting experience, demand for rafting, product cost, and service cost. 2) The factors influencing the demand for water tourism by rafting included the factors of water transportation and the factors of tourism, respectively. From the results of the study, it was found that the involved agencies and rafting entrepreneurs should pay attention to the standards of water transportation by rafting. To clarify, there should be a law identifying the characteristics of the rafts or tourist/passenger boats in terms of suitability and safety for both the tourists and service providers.